Perbedaan Manajemen Konflik pada Atlet Taekwondo Laki-laki dan Perempuan di Provinsi DIY - Mustaqim Setyo Ariyanto; Nurul Az’zahra Garwan; Tri Winarsih (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the differences in conflict management between male and female taekwondo athletes in the Special Region of Yogyakarta (DIY). The research method used is a quantitative approach with a descriptive design. The sample consisted of 112 taekwondo athletes from various regencies/cities in DIY. Data were collected using a questionnaire that measured conflict management styles. The data were analyzed using the analysis of variance (ANOVA) technique. The hypothesis test results show a highly significant difference in conflict management with a significance value of 0.000. The findings reveal that female taekwondo athletes have higher conflict management scores compared to male athletes, with a mean score of 70.40 for females and 63.02 for males. This indicates that female taekwondo athletes possess better conflict management styles than male taekwondo athletes.